The Dynamics Of Forgiveness In Victims Of Dating Violence - Dinda Sundari (Journal Basic Science and Technology, 2020)
This study investigates the dynamics of forgiveness to the victims of dating violence. Forgiveness is an intraphysical process to release unforgiveness but not the same as conflicts resolution (Worthington and Wade, 1999). The research method using qualitative research with purposive sampling technique with two respondents. The result of this study found that both respondents experienced dissonance with different dynamics before forgiveness. The dissonance that occurred in the first respondent was caused by the fear of being abandoned but did not want to continue being entangled in the sexual abuse condition so as to try to find out the living conditions of people who had experienced sexual abuse and chose forgiveness for their conditions. Dissonance experienced by respondent II when she was angry with transgression I but transgressor I tried to apologize and want to change. But re-enslaved cycle conditions forgiveness back after choosing end with conditions forgiveness on the first dating violence. Respondent I chose decisional forgiveness and respondent II chose emotional forgiveness.